Implementasi Strategi Komunikasi Surya Citra Media pada Tiktok @indosiar_sports - Priharsa, Amir Taqiyuddin; Wijaksono, Dimas Satrio (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Surya Citra Televisi is a national private television station in Indonesia founded on August 24, 1990, in Surabaya, later moved to Jakarta. PT INDOSIAR VISUAL MANDIRI is known to all Indonesians for its flagship programs such as soap operas, infotainment, sports, and special events. Social media Sports Indosiar is an essential aspect in promoting the programs at INDOSIAR. The presence of INDOSIAR social media creates interactions between the @indosiar_sports account and TikTok users, influencing engagement on the account. To achieve engagement targets, content is crucial for increasing the engagement of the TikTok @indosiar_sports account. This research aims to provide insight into the selection and content creation process to offer broad reach to TikTok users, especially followers of @indosiar_sports. The theoretical basis includes Communication Strategy, Marketing Communication, Social Media Content, The Circular Model of SoMe, TikTok, and Engagement. The data collection methods used are quantitative and qualitative, observation, and documentation.